Quality assessment system in construction (QLASSIC) at PB Sentral and KP Perdana sites at Kuala Terengganu / Fatin Nabila Othman - Othman, Fatin Nabila (Universiti Teknologi MARA, Perak, 2015)
The quality of workmanship is an important aspect in construction work and will be affected if there are no proper standards of quality. Thus, CIDB took the initiative to improve the quality of construction work by introducing the system of Quality Assessment System in Construction (QLASSIC). This report was conducted to explain the contributors to the low quality of construction works at Kuala Terengganu. Besides that, it covers the methods of QLASSIC, and the elements involved in the quality assessment which is focused on architectural works. The architectural works which more to finishes works in the building. Finally, PMINT are expected to increase their efforts in introducing QLASSIC for every project and can improve the quality of work by referencing the guidelines as set by QLASSIC.